Program Gastizi 1000 dalam meningkatkan kapasitas kader Posyandu - Rachma Purwanti (AcTion: Aceh Nutrition Journal, 2019)
Posyandu cadres are the main actor of UKBM. "Prevention of Stunting with Nutritional Improvement on the 1000 days of life (GASTIZI 1000)” program has purpose to increase the posyandu cadre capasity at Ngarap-arap Village. This research aims to analyze the effectivity of GASTIZI 1000 program  to improve the capacity of the posyandu cadres. This research uses a quasi experimental approach with one group pre test-post test design.  This research was conducted during July – August 2018. Topics presenting in the GASTIZI 1000 program are about Stunting and the nutritional improvement at the 1000 days of life. Subjects are chosen by the total sampling method (All of posyandu cadre at Ngarap-arap village that are willingness to join the GASTIZI 1000 program), 22 people from 6 Hamlet in Ngarap-arap village. Characteristic and cadre knowledge were collected by pre test-post test questionnaire. Skill of cadre to monitor the nutritional status of children was collected by observation and interview. Data were compiled by SPSS software. Then analyzed by univariate and bivariate test with related samples wilcoxon signed rank test. The results showed the averaged  score of cadres knowledge before the GASTIZI 1000 program is 51,8 and after program is 61,5. Bivariate test shows an increased in cadres knowledge after program (p = 0,001). Conclusions, there was an increased in knowledge and skills of cadres about stunting and nutrition during 1000 days of life after following the program. Kader Posyandu merupakan penggerak utama Upaya Kesehatan Bersumberdaya Masyarakat (UKBM). Program “Cegah Stunting dengan Perbaikan Gizi pada 1000 HPK (GASTIZI 1000)” bertujuan untuk meningkatkan kapasitas dari kader Posyandu di Desa Ngarap-arap. Penelitian bertujuan untuk menganalisis efektifitas Program GASTIZI 1000 dalam meningkatkan kapasitas kader posyandu. Penelitian berdesain quasi experimental, dengan rancangan one group pre test-post test design.  Penelitian dilakukan selama bulan Juli – Agustus 2018. Topik yang disampaikan dalam program GASTIZI 1000 yaitu mengenai Stunting dan pentingnya gizi pada periode 1000 HPK. Subjek dipilih dengan metode total sampling yaitu seluruh kader posyandu di Desa Ngarap-arap yang bersedia mengikuti program GASTIZI 1000 HPK sebanyak 22 orang. Pengumpulan data karakteristik dan pengetahuan kader dilakukan dengan instrumen kuesioner pre test-post test. Data keterampilan kader dalam pemantauan status gizi stunting pada balita dikumpulkan dengan observasi dan wawancara terhadap subjek. Data diolah dengan software SPSS. Selanjutnya data dianalisis dengan uji univariat dan bivariat dengan related samples wilcoxon signed rank test. Hasil penelitian menunjukkan terdapatnya peningkatan pengetahuan kader setelah diberikan program GASTIZI 1000 (p=0,001). Kesimpulan, terdapat peningkatan pengetahuan dan keterampilan kader mengenai stunting dan gizi 1000 HPK setelah mengikuti program GASTIZI.